Sistem Informasi Pola Diet Bebas Gluten Dan Kasein Untuk Anak Hiperaktif - Maslihah; Imam Wahyu Budi Utomo (Melek IT : Information Technology Journal, 2017)
To realize a child that is useful in national development required continuous supervision of the family, especially the parents but due to lack of parental knowledge about gluten and casein as allergens for hyperactive children. And the minimum of parental knowledge about the nutritional needs that must be given to children with hyperactivity disorder and thus require considerable time to the process of handling. Adjusting diet is one way to provide nutrition to patients who should have been hyperactive. Based on the above problems I aim to create a web-based information system called. " Information System Gluten and Casein Free Diet For Children Hyperactive " by using Prototype.